TI_GERICHTE 15.2021.138 vom 4. April 2022 , Esecuzione del sequestro diretto contro una persona giuridica. Minimo vitale - TI Tribunale d'appello (2022)
Esecuzione del sequestro diretto contro una persona giuridica. Minimo vitale